Clinical relevance of virological verification methods for the etiology of infectious mononucleosis - O. I. Demina; D. S. Tikhomirov; T. A. Chebotareva; L. N. Mazankova; T. A. Tupoleva (LLC "Diagnostics and Vaccines", 2020)
Purpose: to justify the need to use at least two methods (direct and indirect) for reliable laboratory decoding of infectious mononucleosis. Materials and methods. We observed 107 children with infectious mononucleosis. Deciphering the etiology was carried out using ELISA (We determined IgM VCA-EBV, IgG EA-EBV, IgG EBNA-EBV, IgM CMV, IgG CMV in serum) and PCR (We determined investigated viral DNA (EBV, CMV, HHV 6) in peripheral blood mononuclear cells). Results: In the structure of infectious mononucleosis, EBV remains the leading infection: 82 children (76.6%). In case of reactivated EBV infection, the isolated use of the ELISA method does not limit the possibility of interpreting the results without additional evaluation of the test results by PCR. A significantly level of viral DNA concentration in the examined children has not been established. The detection frequencies of EBV DNA and HHV 6 DNA by PCR are not mutually independent (p < 0.001). Detection of one of the viruses reduces the chance of detecting another virus (OR = 0.133; 95% CI from 0.0537 to 0.3273, p < 0.0001).